Similarities and differences between multisystem inflammatory syndrome in children and Kawasaki disease – clinical presentations, laboratory features and treatment - Czarkowski, Marcin; Gorczyca, Kamila; Grodkiewicz, Maria; Słupczyńska, Aleksandra; Urbaś, Weronika; Podgórska, Klaudia; Puła, Aleksandra; Artykiewicz, Klaudia; Krzysiek, Urszula; Kozieł, Paweł; et al. (Journal of Education, Health and Sport, 2022)
Children infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are mostly asymptomatic or have mild symptoms. However SARS-CoV-2 is also associated with a recently widely reported pediatric systemic vasculitis. This multisystem inflammatory syndrome in children (MIS-C) is still poorly understood, further information and studies are urgently needed. MIS-C has features that overlap with many known multisystem inflammatory diseases, especially Kawasaki disease. In this review, we are comparing MIS-C associated with COVID-19 and Kawasaki disease. We are searching for similarities and differences based on clinical manifestations, diagnosis, and treatment. MIS-C jest stosunkowo nowym zespołem chorobowym, związanym z zakażeniem SARS-CoV-2. Nadal wymaga przeprowadzenia dalszych badań z perspektywy globalnej, w celu zrozumienia jego patogenezy, przebiegu i potencjalnych skutków. Chociaż objawy kliniczne MIS-C i KD mogą się pokrywać, wydają się być dwiema odrębnymi jednostkami klinicznymi i możemy spróbować je rozróżnić na podstawie objawów wspomnianych powyżej.